1981
DOI: 10.1620/tjem.133.81
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potentials elicited by mechanical and electrical stimulation of each single pain or tactile spot of the skin.

Abstract: Single pain and tactile spots on the dorsum of the right hand in man were stimulated by electric pulses and mechanical taps using a needle to . a pain spot and a horse tail bristle to a tactile one. Somatosensory evoked potentials (SEPs) and far field potentials (FFPs) were observed in three volunteers by averaging of 200 or 400 samples of responses recorded from scalp points corresponding to the left and right somatosensory areas (LSA and RSA). For SEP measurements, the difference between responses at LSA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, it may also represent a difference in the saliency between an innocuous control and a noxious stimulation (Iannetti and Mouraux 2010; Legrain et al 2011). The vertex potential following mechanical stimulation found in the present study and reported by others (Bromm and Scharein 1982; Iannetti et al 2007; Yamauchi et al 1981) has a shorter latency (80–280 ms) than that following laser stimulation (200–380 ms; Cruccu et al 2008; Treede et al 2003) but is nevertheless consistent with Aδ activation. Contact heat- and laser-evoked potentials are mediated by thermonociceptive cutaneous fibers, and it is not surprising that the mechanonociceptive evoked responses reported have a shorter latency.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it may also represent a difference in the saliency between an innocuous control and a noxious stimulation (Iannetti and Mouraux 2010; Legrain et al 2011). The vertex potential following mechanical stimulation found in the present study and reported by others (Bromm and Scharein 1982; Iannetti et al 2007; Yamauchi et al 1981) has a shorter latency (80–280 ms) than that following laser stimulation (200–380 ms; Cruccu et al 2008; Treede et al 2003) but is nevertheless consistent with Aδ activation. Contact heat- and laser-evoked potentials are mediated by thermonociceptive cutaneous fibers, and it is not surprising that the mechanonociceptive evoked responses reported have a shorter latency.…”
Section: Discussionsupporting
confidence: 83%
“…The N peak evoked by the lance and the sham control is comparable to that evoked by mechanical pinprick stimulation (Bromm and Scharein 1982; Iannetti et al 2007; Yamauchi et al 1981). As with our findings, this peak did not distinguish innocuous from noxious stimulation and is therefore likely to arise from Aβ tactile afferent input.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, while receptor activation could account for some of the latency difference in our study, the delay for balloon inflation probably accounts for most of the latency difference. The CEP amplitude following electrical and mechanical CEPs has varied between studies, with mechanically evoked CEPs being reported as having a smaller, 29 similar, 14 or larger 30 amplitude than electrically evoked CEPs. However, as no attempt was made in these studies to control for the intensity of electrical and mechanical stimulation, it is difficult to interpret the reported amplitude differences.…”
Section: Discussionmentioning
confidence: 99%